Refining Single-Atom Catalytic Kinetics for Tumor Homologous-Targeted Catalytic Therapy - Liu, Hengke; Lei, Shan; Li, Hongyu; Wu, Jiayingzi; He, Ting; Lin, Jing; Huang, Peng (Nano-Micro Letters, 2025)
Single-atom nanozymes (SAzymes) hold significant potential for tumor catalytic therapy, but their effectiveness is often compromised by low catalytic efficiency within tumor microenvironment. This efficiency is mainly influenced by key factors including hydrogen peroxide (H2O2) availability, acidity, and temperature. Simultaneous optimization of these key factors presents a significant challenge for tumor catalytic therapy. In this study, we developed a comprehensive strategy to refine single-atom catalytic kinetics for enhancing tumor catalytic therapy through dual-enzyme-driven cascade reactions. Iridium (Ir) SAzymes with high catalytic activity and natural enzyme glucose oxidase (GOx) were utilized to construct the cascade reaction system. GOx was loaded by Ir SAzymes due to its large surface area. Then, the dual-enzyme-driven cascade reaction system was modified by cancer cell membranes for improving biocompatibility and achieving tumor homologous targeting ability. GOx catalysis reaction could produce abundant H2O2 and lower the local pH, thereby optimizing key reaction-limiting factors. Additionally, upon laser irradiation, Ir SAzymes could raise local temperature, further enhancing the catalytic efficiency of dual-enzyme system. This comprehensive optimization maximized the performance of Ir SAzymes, significantly improving the efficiency of catalytic therapy. Our findings present a strategy of refining single-atom catalytic kinetics for tumor homologous-targeted catalytic therapy. Highlights: 1 Developed a dual-enzyme cascade system integrating iridium single-atom nanozymes with glucose oxidase, optimizing hydrogen peroxide production, acidity, and temperature within the tumor microenvironment to markedly improve catalytic therapy efficacy. 2 Functionalized the cascade reaction system with cancer cell membranes to achieve homologous targeting and high biocompatibility, ensuring accurate accumulation at tumor sites while minimizing off-target effects.